1997
DOI: 10.1302/0301-620x.79b4.6940
|View full text |Cite
|
Sign up to set email alerts
|

The behavioural response to whiplash injury

Abstract: Thirty-five patients were managed operatively after failure of an anterior cervical discectomy and arthrodesis. Failure was classified as the absence of fusion without deformity but with neck pain or radiculopathy, or both; the absence of fusion after anterior or posterior dislodgment of the graft; or kyphosis due to collapse of the graft or to an unrecognized posterior soft-tissue injury. Twenty-three patients had failure of the arthrodesis without deformity (with neck pain only, neck and arm pain, radiculopa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
35
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(37 citation statements)
references
References 31 publications
1
35
0
1
Order By: Relevance
“…Four previous whiplash studies have used methods similar enough for some comparison to be made. 32,33,36,37 Gargan et al 36 found a recovery rate of 29% at three months (15 of 52), and Radanov et al 37 found a recovery rate of 56% (66 of 117) at three months and 69% (81 of 117) at six months. Overall, the findings of the current study fall within the range of these two previous studies, however it should be noted that the measurement methods were different in these two studies and recovery was used as the outcome rather than functional recovery.…”
Section: Discussionmentioning
confidence: 99%
“…Four previous whiplash studies have used methods similar enough for some comparison to be made. 32,33,36,37 Gargan et al 36 found a recovery rate of 29% at three months (15 of 52), and Radanov et al 37 found a recovery rate of 56% (66 of 117) at three months and 69% (81 of 117) at six months. Overall, the findings of the current study fall within the range of these two previous studies, however it should be noted that the measurement methods were different in these two studies and recovery was used as the outcome rather than functional recovery.…”
Section: Discussionmentioning
confidence: 99%
“…63 It is now also speculated that some individuals are less able to cope with musculoskeletal disorders and, thus, may be slower in recovery from whiplash injury. 16 Identifying the etiology of whiplash injury has been proven difficult, however, in our study, we aimed to investigate the cause of whiplash injury in the study group by objectively scoring the severity of the injuries sustained, using AIS and ISS. AIS is grading the severity of individual injury in 6 defined anatomic regions: 1, minor injury; and 6, unsurvivable injury.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is conflicting evidence about how soon or how frequently symptoms of depression occur after whiplash, and whether such symptoms resolve over time or increase in those whose pain persists. For example, Mayou et al 7 found that approximately 40% of patients had depressive symptomatology within 3 months of whiplash injury, whereas Gargan et al 8 reported no early elevations in psychological distress but increasing distress among whiplash patients failing to recover by 3 months. Wenzel et al 9 reported more depressive symptoms in those whose whiplash had occurred more than 2 years previously, but not in the more recently injured; and Richter et al 10 found that those with more severe or longer duration of pain had greater depressive symptomatology at 6 months.…”
mentioning
confidence: 99%